Traditional Chinese medicine constitution and cardiometabolic multimorbidity: a nationwide cross-sectional study in older adults - Chen, Ran; Li, Hou-Qin; Xia, Jing; He, Fei-Yu; Zhang, Yan; Wang, Zheng; Zhang, Hong-Yi; Yang, Yao-Ming; Bai, Ming-Hua; Ni, Cheng (Frontiers in Public Health, 2026)
ObjectiveCardiometabolic multimorbidity (CMM), defined as the coexistence of two or more cardiometabolic diseases, is increasingly prevalent in older adults. Traditional Chinese medicine (TCM) constitution may influence individual susceptibility and provide complementary approaches for prevention and management. This study aimed to examine the potential association between TCM constitution and CMM to offer novel insights into individualized risk stratification and potential preventive approaches for older adults.MethodsA national cross-sectional study of 24,812 Chinese adults aged ≥60 years was conducted. CMM was defined as having at least two cardiometabolic conditions, including diabetes, stroke, and heart disease. TCM constitutions were assessed using the Chinese Medicine Constitution Questionnaire for the Elderly Edition (CCMQ-EE) and categorized as balanced or eight unbalanced types. The association between TCM constitutions and CMM was analyzed using multivariate logistic regression. To assess the robustness of these associations, inverse probability of treatment weighting (IPTW) based on propensity scores was applied. Stratified analyses assessed subgroup heterogeneity, while tetrachoric correlation and association rule analyses identified constitution co-occurrence patterns.ResultsQi-deficiency constitution (QDC) [OR 1.57, 95% CI 1.21–2.04], Yang-deficiency constitution (YaDC) [OR 1.63, 95% CI 1.35–1.96], Yin-deficiency constitution (YiDC) [OR 1.62, 95% CI 1.33–1.96], and Phlegm-dampness constitution (PDC) [OR 1.40, 95% CI 1.17–1.68] were independently associated with CMM. Associations remained robust after IPTW based on propensity scores. Subgroup analyses showed a stronger association between YaDC and CMM among obese individuals, while the association between YiDC and CMM was more pronounced in participants with central obesity and without hypertension (P for interaction = 0.049). Common mixed constitution patterns in CMM included YiDC with Dampness-heat constitution (DHC), YiDC with Blood stasis constitution (BSC), and PDC with DHC.ConclusionQDC, YaDC, YiDC, and PDC were independently associated with CMM, suggesting that they may represent potential risk factors for its development. Incorporating constitution assessment into routine health evaluations could facilitate the early identification of high-risk subgroups and support the implementation of targeted, constitution-based prevention and management strategies, thereby contributing to reducing the prevalence and burden of CMM in older adults.